Accuracy of Three Screening Tools for Prenatal Substance Use - Coleman-Cowger, Victoria H. (Obstet Gynecol, 2019)
OBJECTIVE: To compare and evaluate the accuracy of three screening tools in identifying illicit drug use and prescription drug misuse among a diverse sample of pregnant women. METHODS: This prospective cross-sectional study enrolled a consecutive sample of 500 pregnant women, stratified by trimester, receiving care in two prenatal clinical settings in Baltimore, Maryland, from January 2017 to January 2018. All participants were administered three index tests: 4P's Plus, NIDA Quick Screen-ASSIST (Modified Alcohol, Smoking and Substance Involvement Screening Test), and the SURP-P (Substance Use Risk Profile-Pregnancy) scale, and administered reference tests (urine and hair drug testing) at the in-person baseline visit. To assess test–retest reliability of the index tests, screening tool administrations were repeated 1 week later by telephone. For each screening tool, sensitivity, specificity, positive predictive value, negative predictive value and test–retest reliability were computed. Results were stratified by age, race, and trimester of pregnancy. RESULTS: Of the 500 enrolled pregnant women, 494 completed the index screening tools, 497 completed reference testing, and 453 underwent test–retest analysis. For the 4P's Plus, sensitivity=90.2% (84.5, 93.8), and specificity=29.6% (24.4, 35.2). For the NIDA Quick Screen-ASSIST, sensitivity=79.7% (71.2, 84.2), and specificity=82.8% (78.1, 87.1). For the SURP-P, sensitivity=92.4% (87.6, 95.8) and specificity=21.8% (17.4, 27.2). Test–retest reliability (phi correlation coefficients) was 0.84, 0.77, and 0.79 for the 4P's Plus, NIDA Quick Screen-ASSIST and the SURP-P, respectively. For all screening tools, there were differences in validity indices by age and race, but no differences by trimester. CONCLUSION: The SURP-P and 4P's Plus had high sensitivity and negative predictive values, making them more ideal screening tests than the NIDA Quick Screen-ASSIST. A clear recommendation for a clinically useful screening tool for prenatal substance use is crucial to allow for prompt and appropriate follow-up and intervention.